Modeling cork yield, thickness, price, and gross income in the Portuguese cork oak montado - Mata, F. (2024)
The cork oak (Quercus suber L.) woodlands, known as montados in Portugal, hold significant economic, cultural, social, and environmental value. They are found in the Mediterranean Sea basin, particularly in the Iberian Peninsula, and sustain various activities like silvopastoralism, with cork being a primary product. Despite its economic significance, challenges such as climate change threaten its sustainability. This study aimed to analyze the edaphoclimatic variables affecting cork yield, thickness, price, and gross income in the Alentejo region of Portugal. A total of 35 farmers were selected for the data collection included in this study. Multivariable linear regressions were performed to establish relationships between cork yield, thickness, price, and gross income as dependent variables, various edaphoclimatic factors, and tree densities. A higher tree density correlates with an increased cork yield but a decreased cork thickness. Soil pH affects cork yield and thickness, with a lower pH favoring higher cork yields but thinner cork. A higher clay and silt content in horizon soil C enhances cork thickness and raises the price but reduces the cork yield. Higher accumulated precipitation and temperatures contribute to higher yields and thicknesses of cork. It is concluded that the relationships between the dependent and the independent variables are complex but partially explainable. Understanding these relationships is paramount to ensure sustainable management practices are adopted that are capable of addressing issues raised in the current context of climate change.